Celebrating Anniversaries - Butler, Petra (Victoria University of Wellington Law Review, 2005)
This article is a summary of the symposium on the Convention on Contracts for the International Sale of Goods ('CISG') in 2005, held in Wellington. The aim of the symposium was to re-familiarise New Zealand's legal community with a part of contract law which seems to have been forgotten or, even worse, which had never gotten into the conscience of New Zealand's legal profession. The first part of the symposium involved the makeup of the CISG and concerns regarding potential barriers to international change. However, the author argues that the symposium papers make clear New Zealand businesses and lawyers should not need to be afraid to choose CISG for their international contracts. The second part of the symposium covered the practical application of the CISG in the day to day business of a lawyer advising his/her client. The author concludes that the seminar papers show New Zealand businesses can only gain from using the CISG as their law for international commercial contracts.